Alienasi Kebijakan Anggaran Provinsi Riau dalam Pencegahan dan Pengendalian Kebakaran Hutan dan Lahan - Muhammad Ichsan Kabullah; Hendri Koeswara; Didi Rahmadi (Jurnal Administrasi dan Kebijakan Publik, 2020)
This article departs from the weak commitment of the Riau Province Government in handling forest fires. Law Number 23 in 2014 stated that the forestry affairs has transferred from regencies/cities to provinces. In that sense, the Riau Province Government should be followed by budget support for fire forest prevention programs. In fact, the budget policies of the Riau Province Government have not shown maximum results for forest fire prevention programs. The research method used a qualitative with case study approach. We used several data collection techniques such as in-depth interviews, observation, documentation and focus group discussions. The findings show that policymakers are alienated from their obligation to prioritize forest fire issues in budgeting. Powerlessness and meaninglessness clearly injure the trust of the public, which often feels suffering when forest fires occur. In the future, it is necessary to make various strategies, including environmental-based budget planning and increasing public participation in monitoring budget planning.